Applying the polygraph by German courts (Academic Journal of Internal Affairs, 2019)
According to the stance of the Federal Court the results of a polygraph test cannot be used as evidences. A part of the courts accepts, and another part refuses it. The author of the article gives an insight into the jurisdictional praxis of the German Federal Court in connection with polygraph tests.
Keywords: polygraph; court; Germany